the correct answer is none of the above
Answer:
Step-by-step explanation:
This is an arithmetic series.
3 , 5 , 7 ,......
Common difference = second term - first term
= 5 - 3
= 2
Answer:
11
Step-by-step explanation:
2x - 6 = 16 (Based on similarity)
2x = 16 + 6
2x = 22
x = 22/2
x = 11
Answer:
Step-by-step explanation:
- (y+9) = 10
Multiply through by -1 gives us
y+9 = -10
Subtract 9 from both sides
y = -19
That's your answer.
If you work it through it satisfies the equation.
That is:
- (-19 +9) = 10
-(-10) = 10
10 = 10
Boo ya!